2013
DOI: 10.1017/s2040174413000172
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to phthalates is associated with decreased anogenital distance and penile size in male newborns

Abstract: Reproductive effects from phthalate exposure have been documented mostly in animal studies. This study explored the association between prenatal exposure to phthalate metabolites, anogenital distance and penile measurements in male newborns in Toluca, State of Mexico. A total of 174 pregnant women provided urine samples for phthalate analysis during their last prenatal visit, and the 73 who gave birth to male infants were included in the study. The 73 male newborns were weighed and measured using standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 30 publications
5
81
1
1
Order By: Relevance
“…Bustamante-Montes et al [42] confirmed these results [42]. They observed an inverse correlation between MEHP concentration in maternal urinary samples during the last trimester of pregnancy and AGD but not ASD, measured 24-48 h after birth, in 73 mother-son pairs in Mexico State.…”
Section: Reviewmentioning
confidence: 75%
“…Bustamante-Montes et al [42] confirmed these results [42]. They observed an inverse correlation between MEHP concentration in maternal urinary samples during the last trimester of pregnancy and AGD but not ASD, measured 24-48 h after birth, in 73 mother-son pairs in Mexico State.…”
Section: Reviewmentioning
confidence: 75%
“…Further follow-up with the cohort indicated that girls exposed to more SLEs in utero also exhibited more masculine play behavior in early childhood than girls exposed to fewer SLEs (84). Numerous epidemiological studies have shown that as in animal models, prenatal exposure to the phthalate DEHP is associated with shorter AGD in infant boys (85)(86)(87)(88). Given that prenatal stress and prenatal phthalate exposure may both influence human AGD, we used Study for Future Families data to examine whether prenatal SLE exposure modifies associations between maternal DEHP metabolite concentrations and infant AGD.…”
Section: Stressful Life Events and Sex-dependent Development In A Prementioning
confidence: 94%
“…Some phthalate diesters are known male reproductive toxicants and exposure at low levels is widespread in many human populations (Duty et al 2003; Bustamante-Montes et al 2013). Effects of phthalates on male reproductive endpoints in rats have been extensively studied and include hypospadias, cryptorchidism, decreased anogenital distance, and decreased testosterone levels in the testes (Mylchreest et al 1998; Gray et al 2000; Clewell et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The origins of TDS are postulated to be due in part to early life-stage exposures to endocrine disrupting compounds such as phthalates (Skakkebaek et al 2001). Due to rising rates of effects described by TDS in some human populations, the possibility that phthalate exposures are contributing to human male reproductive disorders remains a concern (Martino-Andrade and Chahoud 2010; Bustamante-Montes et al 2013). In order to characterize the inherent capacity for the cells in the 3D-TCS to metabolize this important class of male reproductive toxicants, we exposed cells to two known reproductively toxic phthalates, dibutyl phthalate and diethylhexyl phthalate (DBP and DEHP, 100µM) as well as one non-reproductively toxic phthalate, diethyl phthalate (DEP, 150µM).…”
Section: Introductionmentioning
confidence: 99%